(Meth) Acrylic Resin Particles, Carrier Composition, Slurry Composition, And Method For Producing Electronic Component
By designing (meth)acrylic resin particles with specific weight average molecular weight and S atomic concentration, the problem of difficulty in degreasing and filming of ceramic laminates at low temperatures is solved, and efficient and low-cost ceramic laminate production is achieved.
Patent Information
- Application Number
- CN202380062442.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-20
- Filing Date
- 2023-12-08
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve degreasing and filming of the ceramic laminate at low temperatures, and the decomposition temperature of the binder resin is high, so it is impossible to take into account both low-temperature degreasing and filming.
A (meth)acrylic resin particle has a weight average molecular weight of between 1.1 million and 5 million, a weight concentration of S atoms is between 0.0020% and 1.0000%, and a high-strength molded product is formed through specific ester substituents and average particle size design, achieving multilayering and thinning.
It realizes efficient degreasing and filming at low temperatures, reduces the production cost of ceramic laminates, and improves the performance and characteristics of ceramic laminates.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a (meth)acrylic resin particle, a carrier composition, a slurry composition, and a method for producing an electronic component. Background Art
[0002] A laminated ceramic capacitor is known to have a structure including a laminated body in which dielectric layers and internal electrodes are alternately laminated, and a pair of external electrodes disposed so as to sandwich the laminated body. The external electrodes are formed by applying an external electrode conductive paste on the surface of the laminated body and sintering the paste.
[0003] In recent years, in order to reduce the energy consumed in ceramic firing, it is required to reduce the temperature of the degreasing process to remove the binder resin. In addition, the demand for lightweight and high-performance ceramic parts is getting higher and higher, requiring the ceramic green sheet to be thinner and more multilayered during the manufacturing process.
[0004] As such a binder resin for ceramic molding, a methacrylate copolymer obtained by copolymerizing isobutyl methacrylate, 2-ethylhexyl methacrylate, and a methacrylate having a hydroxyl group in a given ratio is described in Patent Document 1. In addition, by using such a binder resin, good moldability and degreasing properties can be exhibited.
[0005] Patent Document 2 describes the use of acrylic resins, polyvinyl butyral resins, polyvinyl acetal resins, ethyl cellulose resins, and the like as binder resins, and particularly describes the use of polyvinyl butyral resins or polyvinyl acetal resins to achieve thinner sheets.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 10-167836
[0009] Patent Document 2: Japanese Patent Application Publication No. 2011-84433 Summary of the invention
[0010] However, although the methacrylate copolymer described in Patent Document 1 can be degreased at low temperatures, the resin itself is brittle and cannot be made into a thin film. In addition, although thin film can be achieved by using a polyvinyl butyral resin as described in Patent Document 2, the decomposition temperature is high and degreasing at low temperatures is not possible. Therefore, a binder resin that can achieve both a low degreasing temperature and a thin film is required.
[0011] The present invention aims to provide a (meth)acrylic resin particle which can produce a high-strength molded product while exhibiting excellent low-temperature decomposition properties, and can achieve further multi-layering and thin-filming, thereby producing a ceramic laminate having excellent properties. Another object is to provide a carrier composition, a slurry composition, and a method for producing an electronic component comprising the (meth)acrylic resin particle.
[0012] Means for solving problems
[0013] The present disclosure (1) provides (meth)acrylic resin particles having a weight average molecular weight of 1,100,000 to 5,000,000, wherein the weight concentration of S atoms in the (meth)acrylic resin particles is 0.0020 wt % to 1.0000 wt %.
[0014] The present disclosure (2) relates to the (meth)acrylic resin particles of the present disclosure (1), wherein the weight concentration of K atoms is 0.002% by weight or more and 1.000% by weight or less.
[0015] The present disclosure (3) relates to the (meth)acrylic resin particles according to the present disclosure (1) or (2), wherein the weight concentration of OH groups is 0.00% by weight or more and 1.50% by weight or less.
[0016] The present disclosure (4) relates to (meth)acrylic resin particles according to any combination of any one of the present disclosures (1) to (3), wherein the average particle size is 0.1 μm or more and 1.0 μm or less.
[0017] The present disclosure (5) relates to (meth)acrylic resin particles according to any combination of any one of the present disclosures (1) to (4), wherein the average carbon number Cp of the ester substituent calculated by the following formula is 3 to 6.
[0018] The average carbon number of the ester substituent of the (meth)acrylic resin Cp=cp1×wp1+cp2×wp2+···+cpn×wpn (cpn: the carbon number of the ester substituent in the segment derived from each (meth)acrylic ester constituting the (meth)acrylic resin, wpn: the weight fraction of the segment derived from each (meth)acrylic ester in the (meth)acrylic resin)
[0019] The present disclosure (6) relates to a carrier composition comprising the (meth)acrylic resin particles according to any one of the present disclosures (1) to (5) and a solvent including an organic solvent.
[0020] The present disclosure (7) relates to the carrier composition of the present disclosure (6), wherein the average carbon number Cs of the ester substituent of the organic solvent calculated by the following formula is 3 to 7.
[0021] The average carbon number of the ester substituent in the organic solvent Cs = cs1×ws1+cs2×ws2+···+csn×wsn (csn: the carbon number of the ester substituent in each organic solvent, wsn: the weight fraction of each organic solvent in the organic solvent)
[0022] The present disclosure (8) relates to the carrier composition of the present disclosure (6) or (7), wherein the ratio (Cs / Cp) of the average carbon number Cs of the ester substituent of the organic solvent to the average carbon number Cp of the ester substituent of the (meth)acrylic resin is 0.3 to 3.0.
[0023] The present disclosure (9) relates to a carrier composition according to any combination of any one of the present disclosures (6) to (8), wherein the solvent further contains 100 ppm by weight or more and 11500 ppm by weight or less of water.
[0024] The present disclosure (10) relates to a slurry composition comprising the carrier composition according to any one of the present disclosures (6) to (9), inorganic particles, and a dispersant.
[0025] The present disclosure (11) relates to a method for producing an electronic component, the method using the slurry composition of the present disclosure (10).
[0026] The present invention is described in detail below.
[0027] The present inventors have found that (meth)acrylic resin particles having a given weight average molecular weight and a weight concentration of S atoms exhibit excellent low-temperature decomposition properties, and when used as a binder for dispersing inorganic particles, a high-strength molded product can be obtained, and further multilayering and thin filming can be achieved. In addition, the inventors have found that by using such (meth)acrylic resin particles, a ceramic laminate having excellent properties can be produced, and thus the present invention has been completed.
[0028] The weight average molecular weight (Mw) of the (meth) acrylic resin particles is 1.1 million or more and 5 million or less. When the weight average molecular weight is 1.1 million or more, the tensile properties of the obtained resin sheet are improved. When the weight average molecular weight is 5 million or less, undissolved matter of the (meth) acrylic resin is less likely to be produced in the obtained resin sheet, and the tensile properties are improved. According to this result, since the strength of the molded product can be improved by setting it to the above range, a green sheet that has been further thinned can be manufactured.
[0029] The weight average molecular weight (Mw) is preferably 1.3 million or more, more preferably 1.5 million or more, and even more preferably 2 million or more. The weight average molecular weight (Mw) is preferably 4.5 million or less, more preferably 4 million or less, and even more preferably 3.5 million or less.
[0030] The weight average molecular weight (Mw) is preferably 1.3 million to 4.5 million, more preferably 1.5 million to 4 million, and even more preferably 2 million to 3.5 million.
[0031] The number average molecular weight (Mn) of the (meth)acrylic resin particles is preferably 300,000 or more, more preferably 600,000 or more, and preferably 2 million or less, more preferably 1.5 million or less. The number average molecular weight (Mn) is preferably 300,000 to 2 million, more preferably 600,000 to 1.5 million.
[0032] In addition, the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the (meth) acrylic resin particles is 1 or more, preferably 5.0 or less, more preferably 4.0 or less, and further preferably 3.5 or less. The Mw / Mn is preferably 1 to 5.0, more preferably 1 to 4.0, and further preferably 1 to 3.5. Within the above range, it is difficult to generate fine undissolved matter in the carrier composition, the strength of the resin sheet can be fully improved, and the generation of voids in the ceramic laminate after firing can be prevented.
[0033] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are average molecular weights based on polystyrene conversion and can be obtained by, for example, GPC measurement using a column LF-804 (manufactured by Showa Denko K.K.) as a column.
[0034] The weight concentration of S atoms contained in the (meth)acrylic resin particles is 0.0020% by weight or more and 1.0000% by weight or less.
[0035] By setting it as the said range, both low-temperature decomposability and the strength of a molded product can be achieved.
[0036] The weight concentration of the S atoms is preferably 0.0030% by weight or more, more preferably 0.0060% by weight or more, and more preferably 0.0100% by weight or more, and preferably 0.9000% by weight or less, more preferably 0.1000% by weight or less, and more preferably 0.0400% by weight or less. The weight concentration of the S atoms is preferably 0.0030 to 0.9000% by weight, more preferably 0.0060 to 0.1000% by weight, and more preferably 0.0100 to 0.0400% by weight. If it is below the upper limit, the low-temperature decomposition property can be made better, and if it is above the lower limit, the tensile properties can be set to a good range and the strength of the molded product can be further improved.
[0037] The weight concentration of S atoms means the ratio of the weight of S atoms in the (meth)acrylic resin structure to the weight of the (meth)acrylic resin particles, and can be calculated based on the following formula.
[0038] Weight concentration of S atoms contained in (meth)acrylic resin particles = [(weight of S atoms contained in all monomers + weight of S atoms contained in all chain transfer agents + weight of S atoms contained in all polymerization initiators) / (weight of all monomers + weight of all chain transfer agents + weight of all polymerization initiators)] × 100
[0039] The weight concentration of S atoms can also be determined by ICP-AES (inductively coupled plasma atomic emission spectrometry).
[0040] The weight concentration of K atoms contained in the (meth)acrylic resin particles is preferably 0.002% by weight or more and preferably 1.000% by weight or less from the viewpoint of the strength of the molded article.
[0041] The weight concentration of the K atoms is more preferably 0.010 wt% or more, more preferably 0.015 wt% or more, and more preferably 0.500 wt% or less, and more preferably 0.030 wt% or less. The weight concentration of the K atoms is preferably 0.002 to 1.000 wt%, more preferably 0.010 to 0.500 wt%, and more preferably 0.015 to 0.030 wt%. If it is below the upper limit, the low-temperature decomposition property can be further improved, and if it is above the lower limit, the tensile properties can be set to a good range and the strength of the molded product can be further improved.
[0042] The weight concentration of K atoms means the ratio of the weight of K atoms in the (meth)acrylic resin structure to the weight of the (meth)acrylic resin particles, and can be calculated based on the following formula.
[0043] Weight concentration of K atoms contained in (meth)acrylic resin particles = [(weight of K atoms contained in all monomers + weight of K atoms contained in all chain transfer agents + weight of K atoms contained in all polymerization initiators) / (weight of all monomers + weight of all chain transfer agents + weight of all polymerization initiators)] × 100
[0044] In addition, the weight concentration of the K atom can also be measured using an atomic absorption spectrophotometer.
[0045] The weight concentration of the OH groups contained in the (meth)acrylic resin particles is preferably 0.00% by weight or more, and preferably 1.50% by weight or less, more preferably 0.50% by weight or less, and further preferably 0.25% by weight or less, from the viewpoint of low-temperature decomposition. The weight concentration of the OH groups is preferably 0.00 to 1.50% by weight, more preferably 0.00 to 0.50% by weight, and further preferably 0.00 to 0.25% by weight.
[0046] The weight concentration of OH groups means the ratio of the weight of OH groups in the (meth)acrylic resin structure to the weight of the (meth)acrylic resin particles, and can be calculated based on the following formula.
[0047] Weight concentration of OH groups contained in (meth)acrylic resin particles = [(weight of OH groups contained in all monomers + weight of OH groups contained in all chain transfer agents + weight of OH groups contained in all polymerization initiators) / (weight of all monomers + weight of all chain transfer agents + weight of all polymerization initiators)] × 100
[0048] The weight concentration of the OH group can also be determined by ESCA analysis using a gas phase chemical modification method.
[0049] The weight concentration of COOH groups in the (meth)acrylic resin particles is not particularly limited, but preferably contains no COOH groups and the weight concentration of COOH groups is 0% by weight from the viewpoint of low-temperature decomposition properties.
[0050] The (meth)acrylic resin particles preferably have an average particle size of 0.1 μm or more and preferably 1.0 μm or less.
[0051] By setting it as the said range, the solubility of a (meth)acrylic-type resin particle can be improved further.
[0052] The average particle size is more preferably 0.2 μm or more, more preferably 0.3 μm or more, and more preferably 0.9 μm or less, and more preferably 0.8 μm or less. The average particle size is preferably 0.1 to 1.0 μm, more preferably 0.2 to 0.9 μm, and more preferably 0.3 to 0.8 μm. The average particle size can be obtained, for example, by measuring the volume average particle size using a laser diffraction / scattering particle size distribution measuring device.
[0053] It should be noted that the above average particle size can be adjusted by the type and amount of the polymerization initiator. For example, there is a tendency that the average particle size becomes smaller if the content of the polymerization initiator is large, and the average particle size becomes larger if the content of the polymerization initiator is small. In addition, there is a tendency that the average particle size becomes smaller if persulfates such as ammonium persulfate and potassium persulfate are used.
[0054] The CV value of the particle size of the (meth)acrylic resin particles is preferably 15% or less, more preferably 12% or less, further preferably 10% or less, and further preferably 8% or less.
[0055] By setting it as said range, the solubility of (meth)acrylic-type resin particle can be improved further. When solubility improves, productivity will improve, and tensile property will improve by reducing undissolved resin.
[0056] The lower limit is not particularly limited, and is, for example, 0%. The CV value of the particle size is preferably 0 to 15%, more preferably 0 to 12%, further preferably 0 to 10%, and further preferably 0 to 8%.
[0057] The CV value can be calculated from the average value and standard deviation of the particle diameters of 100 particles by observing the (meth)acrylic resin particles using a scanning electron microscope. The CV value tends to decrease when a persulfate such as ammonium persulfate or potassium persulfate is used.
[0058] The (meth)acrylic resin particles preferably contain a segment derived from a (meth)acrylic acid ester having 8 or less carbon atoms in the ester substituent.
[0059] In addition, when the carbon number of the said ester substituent is 8 or less, it means that the total number of carbon atoms other than the carbon atoms which constitute the (meth)acryloyl group in (meth)acrylate is 8 or less.
[0060] Examples of the (meth)acrylate in which the ester substituent has 8 or less carbon atoms include (meth)acrylates having a linear, branched, or cyclic alkyl group.
[0061] Examples of the (meth)acrylate having a linear alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, and n-butyl (meth)acrylate.
[0062] Examples of the (meth)acrylate having a branched alkyl group include isopropyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.
[0063] Examples of the (meth)acrylate having a cyclic alkyl group include cyclohexyl (meth)acrylate and benzyl (meth)acrylate.
[0064] In addition, as the (meth)acrylate having 8 or less carbon atoms in the ester substituent, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, (meth)acrylate having a hydroxyl group or a carboxyl group such as (meth)acrylic acid, (meth)acrylate having a glycidyl group, and the like can also be used.
[0065] Examples of the (meth)acrylate having a glycidyl group include glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and 3,4-epoxycyclohexyl (meth)acrylate.
[0066] Among them, (meth)acrylates having a linear alkyl group and (meth)acrylates having a branched alkyl group are preferred. Methyl methacrylate, ethyl methacrylate, and isobutyl methacrylate are more preferred. Furthermore, a combination of a (meth)acrylate having a linear alkyl group and a (meth)acrylate having a branched alkyl group is preferred.
[0067] As the (meth)acrylate having 8 or less carbon atoms in the ester substituent, there may be used (meth)acrylate having 1 to 4 carbon atoms in the ester substituent, or there may be used (meth)acrylate having 5 to 8 carbon atoms in the ester substituent. Among them, there are preferably used (meth)acrylate having 1 to 4 carbon atoms in the ester substituent.
[0068] In addition, the (meth)acrylate having 8 or less carbon atoms in the ester substituent preferably does not include a (meth)acrylate having a glycidyl group.
[0069] The content of the segment of the (meth) acrylic acid ester having a carbon number of 8 or less in the (meth) acrylic resin particles is preferably 40% by weight or more, more preferably 60% by weight or more, and further preferably 80% by weight or more. The upper limit is not particularly limited, but is preferably 100% by weight or less, more preferably 99% by weight or less, and further preferably 98% by weight or less. The content of the segment of the (meth) acrylic acid ester having a carbon number of 8 or less in the ester substituent is preferably 40 to 100% by weight, more preferably 60 to 99% by weight, and further preferably 80 to 98% by weight.
[0070] The content of the above-mentioned segment in the above-mentioned (meth)acrylic resin particles can be calculated based on the ratio of each monomer among the raw materials for producing the (meth)acrylic resin constituting the (meth)acrylic resin particles, relative to 100 parts by weight of the raw material monomers excluding the polymerization initiator and the chain transfer agent.
[0071] The content of the segment derived from the (meth)acrylic acid ester having a branched alkyl group with a carbon number of 8 or less in the ester substituent in the (meth)acrylic resin particles is preferably 30% by weight or more, more preferably 35% by weight or more, and is preferably 70% by weight or less, more preferably 60% by weight or less. The content of the segment derived from the (meth)acrylic acid ester having a branched alkyl group with a carbon number of 8 or less in the ester substituent is preferably 30 to 70% by weight, more preferably 35 to 60% by weight.
[0072] The content of the segment of the (meth) acrylic acid ester having 1 to 4 carbon atoms in the ester substituent in the (meth) acrylic resin particles is preferably 40% by weight or more, more preferably 60% by weight or more, and further preferably 80% by weight or more. The upper limit is not particularly limited, but is, for example, 100% by weight or less. The content of the segment of the (meth) acrylic acid ester having 1 to 4 carbon atoms in the ester substituent is preferably 40 to 100% by weight, more preferably 60 to 100% by weight, and further preferably 80 to 100% by weight.
[0073] The content of the segment of the (meth) acrylic acid ester having 5 to 8 carbon atoms in the ester substituent in the (meth) acrylic resin particles is preferably 60% by weight or less, more preferably 40% by weight or less, and further preferably 20% by weight or less. The lower limit is not particularly limited, but is, for example, 0% by weight or more. The content of the segment of the (meth) acrylic acid ester having 5 to 8 carbon atoms in the ester substituent is preferably 0 to 60% by weight, more preferably 0 to 40% by weight, and further preferably 0 to 20% by weight.
[0074] The content of the segment derived from methyl methacrylate in the (meth)acrylic resin particles is preferably 5% by weight or more, more preferably 10% by weight or more, and is preferably 40% by weight or less, more preferably 30% by weight or less. The content of the segment derived from methyl methacrylate is preferably 5 to 40% by weight, more preferably 10 to 30% by weight.
[0075] The content of the segment derived from ethyl methacrylate in the (meth)acrylic resin particles is preferably 10% by weight or more, more preferably 20% by weight or more, and is preferably 30% by weight or less, more preferably 25% by weight or less. The content of the segment derived from ethyl methacrylate is preferably 10 to 30% by weight, more preferably 20 to 25% by weight.
[0076] The content of the segment derived from n-butyl methacrylate in the (meth)acrylic resin particles is preferably 25% by weight or more, more preferably 30% by weight or more, and is preferably 50% by weight or less, more preferably 40% by weight or less. The content of the segment derived from n-butyl methacrylate is preferably 25 to 50% by weight, more preferably 30 to 40% by weight.
[0077] The content of the segment derived from isobutyl methacrylate in the (meth)acrylic resin particles is preferably 30% by weight or more, more preferably 35% by weight or more, and is preferably 60% by weight or less, more preferably 50% by weight or less. The content of the segment derived from isobutyl methacrylate is preferably 30 to 60% by weight, more preferably 35 to 50% by weight.
[0078] The (meth)acrylic resin particles may have a segment derived from a (meth)acrylic acid ester having 9 or more carbon atoms in an ester substituent.
[0079] The carbon number of the ester substituent is more preferably 10 or more, and is preferably 30 or less, and more preferably 20 or less. The carbon number of the ester substituent is preferably 9-30, and more preferably 10-20.
[0080] Examples of the (meth)acrylate having 9 or more carbon atoms in the ester substituent include (meth)acrylate having a linear or branched alkyl group having 9 or more carbon atoms, and polyalkylene glycol (meth)acrylate.
[0081] Examples of the (meth)acrylate having a linear or branched alkyl group having 9 or more carbon atoms include n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, isolauryl (meth)acrylate, n-stearyl (meth)acrylate, and isostearyl (meth)acrylate.
[0082] Examples of the polyalkylene glycol (meth)acrylate include polyalkylene glycol (meth)acrylates having an ethylene glycol unit, a propylene glycol unit, a butylene glycol unit, and the like.
[0083] The polyalkylene glycol (meth)acrylate may have an alkoxy group at the terminal, or may have an ethylhexyl group at the terminal.
[0084] The polyalkylene glycol (meth)acrylate may have a linear alkylene glycol unit or a branched alkylene glycol unit.
[0085] The content of the segment of the (meth) acrylic acid ester having 9 or more carbon atoms in the ester substituent in the (meth) acrylic resin particles is preferably 60% by weight or less, more preferably 40% by weight or less, and further preferably 20% by weight or less. The lower limit is not particularly limited, but is, for example, 0% by weight or more. The content of the segment of the (meth) acrylic acid ester having 9 or more carbon atoms in the ester substituent is preferably 0 to 60% by weight, more preferably 0 to 40% by weight, and further preferably 0 to 20% by weight.
[0086] Since the content of the segments derived from the acrylic monomer in the (meth)acrylic resin particles is less, the lower the content, the better the low-temperature decomposition property. Therefore, it is preferably 5% by weight or less, and more preferably 1% by weight or less. The lower limit is not particularly limited, but is, for example, 0% by weight or more. The content of the segments derived from the acrylic monomer is preferably 0 to 5% by weight, more preferably 0 to 1% by weight, and further preferably 0% by weight.
[0087] It should be noted that the above-mentioned acrylic monomer means acrylic acid and acrylic acid ester.
[0088] The (meth)acrylic resin particles preferably have an average carbon number Cp of ester substituents calculated by the following formula of 3 or more and 6 or less.
[0089] When the average carbon number Cp is 3 or more, the elongation at break of the obtained resin sheet becomes good and the tensile properties are improved. When the average carbon number Cp is 6 or less, the yield stress becomes high and the tensile properties are improved.
[0090] The average carbon number Cp is more preferably 3.3 or more, and further preferably 4.5 or less. The average carbon number Cp is preferably 3 to 6, and more preferably 3.3 to 4.5.
[0091] Average carbon number of ester substituent Cp = cp1 × wp1 + cp2 × wp2 + ... + cpn × wpn (cpn: carbon number of ester substituent in each (meth)acrylate segment constituting the (meth)acrylic resin, wpn: weight fraction of each (meth)acrylate segment constituting the (meth)acrylic resin)
[0092] The glass transition temperature (Tg) of the (meth)acrylic resin particles is preferably 30° C. or higher and preferably 85° C. or lower.
[0093] By setting it as the said range, the addition amount of a plasticizer can be reduced, and low-temperature decomposition property can be further improved.
[0094] The Tg is more preferably 32°C or higher, further preferably 42°C or higher, and more preferably 80°C or lower, further preferably 75°C or lower. The Tg is preferably 30 to 85°C, more preferably 32 to 80°C, further preferably 42 to 75°C.
[0095] In addition, the said glass transition temperature (Tg) can be measured using a differential scanning calorimeter (DSC) etc., for example.
[0096] The 90 wt % decomposition temperature of the (meth)acrylic resin particles when heated from 30° C. at 5° C. / min is preferably 280° C. or less, more preferably 270° C. or less, and even more preferably 260° C. or less. The lower limit is not particularly limited, but is 30° C. or more, and the lower the more preferred. The 90 wt % decomposition temperature is preferably 30 to 280° C., more preferably 30 to 270° C., and even more preferably 30 to 260° C.
[0097] Examples of a method for producing the (meth)acrylic resin particles include a method of adding an organic solvent or the like to a raw material monomer mixture containing a (meth)acrylic acid ester or the like to prepare a monomer mixed solution, and then adding a polymerization initiator and a chain transfer agent to the obtained monomer mixed solution to copolymerize the raw material monomers.
[0098] The polymerization method is not particularly limited, and examples thereof include emulsion polymerization, suspension polymerization, bulk polymerization, interfacial polymerization, solution polymerization, etc. Among them, emulsion polymerization is preferred.
[0099] Examples of the organic solvent include toluene, ethyl acetate, butyl acetate, amyl acetate, hexyl acetate, ethyl butyrate, butyl butyrate, amyl butyrate, hexyl butyrate, isopropyl alcohol, methyl isobutyl ketone, methyl ethyl ketone, methyl isobutyl ketone, ethylene glycol ethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, trimethylpentanediol monoisobutyrate, butyl carbitol, butyl carbitol acetate, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, Texanol, isophorone, butyl lactate, dioctyl phthalate, dioctyl adipate, benzyl alcohol, phenylpropylene glycol, and cresol. Among them, butyl acetate, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, butyl carbitol acetate, and Texanol are preferred. In addition, butyl acetate, terpineol, terpineol acetate, dihydroterpineol, and dihydroterpineol acetate are more preferred. It should be noted that these organic solvents may be used alone or in combination of two or more.
[0100] Examples of the polymerization initiator include tert-butyl peroxypivalate, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, cyclohexanone peroxide, disuccinic acid peroxide, and the like. Examples of the polymerization initiator include 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] sulfate hydrate, acid mixtures of imidazole-based azo compounds such as 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[N- Water-soluble azo compounds such as [(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 4,4'-azobis-4-cyanovaleric acid, oxygen-containing acids such as potassium persulfate (potassium peroxodisulfate), ammonium persulfate (ammonium peroxodisulfate), sodium persulfate (sodium peroxodisulfate), peroxides such as hydrogen peroxide, peracetic acid, performic acid, and perpropionic acid, etc.
[0101] Among them, it is preferable to use a polymerization initiator containing an S atom or a polymerization initiator containing a K atom. In addition, potassium persulfate, ammonium persulfate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] are preferred, and potassium persulfate and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] are more preferred.
[0102] The amount of the polymerization initiator added is preferably 0.03 parts by weight or more, and preferably 4.0 parts by weight or less, more preferably 0.05 parts by weight or more, and more preferably 3.6 parts by weight or less, relative to 100 parts by weight of the raw material monomer. The amount of the polymerization initiator added is preferably 0.03 to 4.0 parts by weight, and more preferably 0.05 to 3.6 parts by weight, relative to 100 parts by weight of the raw material monomer.
[0103] As the chain transfer agent, a chain transfer agent having a S atom is preferably used, and examples thereof include 3-mercapto-1,2-propanediol, 3-mercapto-1-propanol, 3-mercapto-2-butanol, 8-mercapto-1-octanol, 2-mercaptobenzimidazole, mercaptosuccinic acid, and thioglycolic acid.
[0104] Among them, 3-mercapto-1,2-propanediol is preferably used.
[0105] The amount of the chain transfer agent added is preferably 0.01 parts by weight or more, more preferably 0.02 parts by weight or more, and preferably 10.0 parts by weight or less, more preferably 5.0 parts by weight or less, relative to 100 parts by weight of the raw material monomer. The amount of the chain transfer agent added is preferably 0.01 to 10.0 parts by weight, more preferably 0.02 to 5.0 parts by weight, relative to 100 parts by weight of the raw material monomer.
[0106] The temperature during polymerization is preferably 50° C. or higher, more preferably 60° C. or higher, and is preferably 90° C. or lower, more preferably 80° C. or lower. The temperature during polymerization is preferably 50 to 90° C., more preferably 60 to 80° C.
[0107] The carrier composition can be prepared using the (meth)acrylic resin particles and a solvent including an organic solvent.
[0108] Furthermore, a carrier composition containing the (meth)acrylic resin particles and a solvent including an organic solvent is also one of the present invention.
[0109] The content of the (meth)acrylic resin particles in the carrier composition is preferably 5% by weight or more, more preferably 10% by weight or more, and is preferably 50% by weight or less, more preferably 40% by weight or less. The content of the (meth)acrylic resin particles is preferably 5 to 50% by weight, more preferably 10 to 40% by weight.
[0110] The above-mentioned carrier composition contains an organic solvent.
[0111] Examples of the organic solvent include alcohols such as aliphatic alcohols, glycols, terpene alcohols, and aromatic alcohols, aromatic hydrocarbons, esters, ketones, and N-methylpyrrolidone.
[0112] Examples of the aliphatic alcohols include ethanol, propanol, isopropanol, heptanol, octanol, decanol, tridecanol, lauryl alcohol, tetradecanol, cetyl alcohol, 2-ethyl-1-hexanol, octadecyl alcohol, hexadecanol, oleyl alcohol, Texanol, 2-butyl-2-ethyl-1,3-propanediol, and neopentyl glycol.
[0113] Examples of the diols include ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, ethylene glycol monoethyl ether acetate, trimethylpentanediol monoisobutyrate, butyl carbitol acetate, Texanol, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, and ethylene glycol ethyl ether.
[0114] Examples of the terpene alcohols include terpineol, dihydroterpineol, terpineol acetate, and dihydroterpineol acetate.
[0115] Examples of the aromatic alcohols include benzyl alcohol and the like.
[0116] Examples of the aromatic hydrocarbons include toluene and the like.
[0117] Examples of the esters include methyl acetate, ethyl acetate, butyl acetate, hexyl acetate, dodecyl acetate, isoamyl acetate, butyl butyrate, butyl lactate, dioctyl phthalate, and dioctyl adipate.
[0118] Examples of the ketones include methyl isobutyl ketone, methyl ethyl ketone, methyl isobutyl ketone, and isophorone.
[0119] Among them, esters are preferred, methyl acetate, ethyl acetate, butyl acetate, hexyl acetate, and dodecyl acetate are more preferred, and ethyl acetate, butyl acetate, and hexyl acetate are further preferred.
[0120] The average carbon number Cs of the ester substituent of the organic solvent calculated by the following formula is preferably 3 or more and 7 or less.
[0121] When the content is within the above range, the affinity between the acrylic resin and the organic solvent becomes high, and the tensile performance can be improved.
[0122] The average carbon number Cs is more preferably 3.5 or more, and more preferably 4.5 or less. The Cs is preferably 3 to 7, and more preferably 3.5 to 4.5.
[0123] The average carbon number of the ester substituent in the organic solvent Cs = cs1×ws1+cs2×ws2+···+csn×wsn (csn: the carbon number of the ester substituent in each organic solvent, wsn: the weight fraction of each organic solvent in the organic solvent)
[0124] The ratio (Cs / Cp) of the average carbon number Cs of the ester substituent of the organic solvent in the carrier composition to the average carbon number Cp of the ester substituent of the (meth)acrylic resin particles is preferably 0.3 or more and 3.0 or less from the viewpoint of the strength of the molded article.
[0125] If it is within the above range, the affinity of the (meth)acrylic resin particles to the organic solvent becomes high, and the tensile performance can be improved. In addition, if it is within the above range, the affinity of the (meth)acrylic resin particles to the organic solvent becomes high, and the solubility of the resin can be improved.
[0126] The above Cs / Cp is more preferably 0.5 or more, and more preferably 1.5 or less. The above Cs / Cp is preferably 0.3 to 3.0, and more preferably 0.5 to 1.5.
[0127] The content of the organic solvent in the carrier composition is not particularly limited, but is preferably 65% by weight or more, more preferably 70% by weight or more, and is preferably 90% by weight or less, more preferably 85% by weight or less. The content of the organic solvent is preferably 65 to 90% by weight, more preferably 70 to 85% by weight.
[0128] In the above-mentioned carrier composition, it is preferred that the solvent further contains water.
[0129] The content of the water in the solvent is preferably 100 ppm by weight or more and preferably 11500 ppm by weight or less.
[0130] By including water in the above range, fusion with the dispersant is improved, and low-temperature decomposability is further improved.
[0131] The water content in the solvent is more preferably 300 ppm by weight or more, more preferably 400 ppm by weight or more, and more preferably 1000 ppm by weight or less, more preferably 700 ppm by weight or less. The water content is preferably 100 to 11500 ppm by weight, more preferably 300 to 1000 ppm by weight, and more preferably 400 to 700 ppm by weight.
[0132] The water content in the carrier composition is preferably 100 ppm by weight or more and preferably 10,000 ppm by weight or less. The water content is preferably 100 to 10,000 ppm by weight.
[0133] The content of the above-mentioned solvent in the above-mentioned carrier composition is not particularly limited, but is preferably 65% by weight or more, more preferably 70% by weight or more, and is preferably 90% by weight or less, more preferably 85% by weight or less. The content of the above-mentioned solvent is preferably 65 to 90% by weight, more preferably 70 to 85% by weight.
[0134] Examples of a method for producing the carrier composition include a method of adding an organic solvent, water, etc. to the (meth)acrylic resin particles obtained by the above method and stirring and mixing the mixture.
[0135] The carrier composition, inorganic particles and dispersant described above can be used to prepare a slurry composition.
[0136] Furthermore, a slurry composition containing the above-mentioned carrier composition, inorganic particles and a dispersant is also one of the present invention.
[0137] The content of the (meth)acrylic resin particles in the slurry composition is preferably 3% by weight or more, preferably 5% by weight or more, and preferably 10% by weight or less, preferably 8% by weight or less. The content of the (meth)acrylic resin particles is preferably 3 to 10% by weight, more preferably 5 to 8% by weight.
[0138] The content of the organic solvent in the slurry composition is preferably 25 wt % or more, preferably 30 wt % or more, and preferably 70 wt % or less, preferably 60 wt % or less. The content of the organic solvent is preferably 25-70 wt %, more preferably 30-60 wt %.
[0139] The water content in the slurry composition is preferably 30 ppm by weight or more, more preferably 1000 ppm by weight or more, and further preferably 5000 ppm by weight or more, and is preferably 15000 ppm by weight or less, more preferably 10000 ppm by weight or less, and further preferably 7000 ppm by weight or less. The water content is preferably 30 to 15000 ppm by weight, more preferably 1000 to 10000 ppm by weight, and further preferably 5000 to 7000 ppm by weight.
[0140] The content of the solvent in the slurry composition is preferably 25 wt % or more, preferably 30 wt % or more, and preferably 70 wt % or less, preferably 60 wt % or less. The content of the solvent is preferably 25-70 wt %, more preferably 30-60 wt %.
[0141] The slurry composition contains inorganic particles.
[0142] The inorganic particles are not particularly limited, and examples thereof include glass powder, ceramic powder, phosphor particles, silicon oxide, and metal particles.
[0143] The above-mentioned glass powder is not particularly limited, and examples thereof include glass powders of bismuth oxide glass, silicate glass, lead glass, zinc glass, boron glass, etc., and glass powders of various silicon oxides such as CaO-Al2O3-SiO2 system, MgO-Al2O3-SiO2 system, and LiO2-Al2O3-SiO2 system.
[0144] In addition, as the above-mentioned glass powder, a SnO-B2O3-P2O5-Al2O3 mixture, a PbO-B2O3-SiO2 mixture, a BaO-ZnO-B2O3-SiO2 mixture, a ZnO-Bi2O3-B2O3-SiO2 mixture, a Bi2O3-B2O3-BaO-CuO mixture, a Bi2O3-ZnO-B2O3-Al2O3-SrO mixture, a ZnO-Bi2O3-B2O3 mixture, a Bi2O3-SiO2 mixture, a P2O5-Na2O-CaO-BaO-Al2O3-B2O3 mixture, a P2O5-SnO mixture, a P2O5-SnO-B2O3 mixture Glass powders include a mixture of P2O5-SnO-SiO2, a mixture of CuO-P2O5-RO, a mixture of SiO2-B2O3-ZnO-Na2O-Li2O-NaF-V2O5, a mixture of P2O5-ZnO-SnO-R2O-RO, a mixture of B2O3-SiO2-ZnO, a mixture of B2O3-SiO2-Al2O3-ZrO2, a mixture of SiO2-B2O3-ZnO-R2O-RO, a mixture of SiO2-B2O3-Al2O3-RO-R2O, a mixture of SrO-ZnO-P2O5, a mixture of SrO-ZnO-P2O5, a mixture of BaO-ZnO-B2O3-SiO2, etc. It should be noted that R is an element selected from Zn, Ba, Ca, Mg, Sr, Sn, Ni, Fe and Mn.
[0145] Particularly preferred are lead-free glass powders such as glass powder of a PbO-B2O3-SiO2 mixture, a lead-free BaO-ZnO-B2O3-SiO2 mixture, or a ZnO-Bi2O3-B2O3-SiO2 mixture.
[0146] The above-mentioned ceramic powder is not particularly limited, and examples thereof include alumina, ferrite, zirconium oxide, zircon, barium zirconate, calcium zirconate, titanium oxide, barium titanate, strontium titanate, calcium titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, lead zirconate titanate, aluminum nitride, silicon nitride, boron nitride, boron carbide, barium stannate, calcium stannate, magnesium silicate, mullite, steatite, cordierite, forsterite, etc.
[0147] In addition, ITO, FTO, niobium oxide, vanadium oxide, tungsten oxide, strontium lanthanum manganate (Japanese: ランタンストロンチウムマンガナイト), Lanthanum strontium cobalt ferrite (Japanese: ランタンストロンチウムコバルトフェライト), yttrium-stabilized zirconia, gadolinium-doped cerium oxide, nickel oxide, lanthanum chromate, etc.
[0148] The phosphor particles are not particularly limited, and for example, blue phosphors, red phosphors, green phosphors, etc., which are known as phosphors for displays, can be used as phosphor materials. For example, MgAl 10 O 17 :Eu、Y2SiO5:Ce series、CaWO4:Pb series、BaMgAl 14 O 23 :Eu series, BaMgAl 16 O 27 :Eu series, BaMg2Al 14 O 23 :Eu series, BaMg2Al 14 O 27 :Eu-based, ZnS:(Ag, Cd)-based phosphor substances. As red phosphor substances, for example, Y2O3:Eu-based, Y2SiO5:Eu-based, Y3Al5O 12 :Eu series, Zn3(PO4)2:Mn series, YBO3:Eu series, (Y,Gd)BO3:Eu series, GdBO3:Eu series, ScBO3:Eu series, LuBO3:Eu series. As green phosphor materials, for example, Zn2SiO4:Mn series, BaAl 12 O 19 :Mn series, SrAl 13 O 19 : Mn series, CaAl 12 O 19 :Mn series, YBO3:Tb series, BaMgAl 14 O 23 :Mn series, LuBO3:Tb series, GdBO3:Tb series, ScBO3:Tb series, Sr6Si3O3Cl4:Eu series phosphor substances. In addition, ZnO:Zn series, ZnS:(Cu,Al) series, ZnS:Ag series, Y2O2S:Eu series, ZnS:Zn series, (Y,Cd)BO3:Eu series, BaMgAl 12 O 23 : Eu-based phosphor material.
[0149] The metal particles are not particularly limited, and examples thereof include powders containing iron, copper, nickel, palladium, platinum, gold, silver, aluminum, tungsten, and alloys thereof.
[0150] In addition, metals such as copper and iron that have good adsorption characteristics with carboxyl groups, amino groups, amide groups, etc. and are easily oxidized can also be used appropriately. These metal particles may be used alone or in combination of two or more.
[0151] In addition, various carbon blacks, carbon nanotubes, and the like may be used as the metal particles other than the metal complex.
[0152] The inorganic particles preferably contain lithium or titanium. Specifically, examples thereof include low melting point glass such as LiO2•Al2O3•SiO2 inorganic glass, Li2S-M x S y (M=B, Si, Ge, P) and other lithium chalcogenide glasses, lithium cobalt composite oxides such as LiCeO2, lithium manganese composite oxides such as LiMnO4, lithium nickel composite oxides, lithium vanadium composite oxides, lithium zirconium composite oxides, lithium hafnium composite oxides, lithium silicophosphate (Li 3.5 Si 0.5 P 0.5 O4), lithium titanium phosphate (LiTi2(PO4)3), lithium titanate (Li4Ti5O 12 )、Li 4 / 3 Ti 5 / 3O4, LiCoO2, lithium germanium phosphate (LiGe2 (PO4) 3), Li2-SiS glass, Li4GeS4-Li3PS4 glass, LiSiO3, LiMn2O4, Li2S-P2S5 glass • ceramics, Li2O-SiO2, Li2O-V2O5-SiO2, LiS-SiS2-Li4SiO4 glass, LiPON and other ion conductive oxides, Li2O-P2O5-B2O3, Li2O-GeO2Ba and other lithium oxide compounds, Li x Al y Ti z (PO4) 3 series glass, La x Li y TiO z Glass, Li x Ge y P z O4 series glass, Li7La3Zr2O 12 Glass, Li v Si w P x S y Cl z Glass, lithium niobium oxides such as LiNbO3, lithium aluminum oxide compounds such as Li-β-alumina, Li 14 Lithium zinc oxides such as Zn(GeO4)4, etc.
[0153] The average particle size of the inorganic particles is preferably 0.01 μm or more and preferably 5 μm or less, more preferably 0.05 μm or more and more preferably 3 μm or less, further preferably 0.1 μm or more and further preferably 1 μm or less. The average particle size of the inorganic particles is preferably 0.01 to 5 μm, more preferably 0.05 to 3 μm, further preferably 0.1 to 1 μm.
[0154] The average particle size can be determined, for example, by measuring the volume average particle size using a laser diffraction / scattering particle size distribution analyzer.
[0155] The content of the inorganic particles in the slurry composition is preferably 30 wt % or more and preferably 90 wt % or less. Within the above range, the slurry composition has sufficient viscosity, can have excellent coating properties, and can also have excellent dispersibility of the inorganic particles.
[0156] The content of the inorganic particles is more preferably 40% by weight or more, and more preferably 70% by weight or less. The content of the inorganic particles is preferably 30 to 90% by weight, and more preferably 40 to 70% by weight.
[0157] The slurry composition contains a dispersant.
[0158] As the above-mentioned dispersant, for example, fatty acids, aliphatic amines, alkanolamides, and phosphoric acid esters are suitable. In addition, a silane coupling agent or the like may also be blended.
[0159] The fatty acid is not particularly limited, and examples thereof include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, capric acid, caprylic acid, and coconut fatty acid; and unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, sorbic acid, tallow fatty acid, and castor oil hydrogenated fatty acid. Among them, lauric acid, stearic acid, and oleic acid are suitable.
[0160] The aliphatic amine is not particularly limited, and examples thereof include laurylamine, myristicamine, cetylamine, stearylamine, oleylamine, alkyl (coconut) amine, alkyl (hydrogenated tallow) amine, alkyl (tallow) amine, and alkyl (soy) amine.
[0161] The alkanolamide is not particularly limited, and examples thereof include coconut fatty acid diethanolamide, tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.
[0162] The phosphoric acid ester is not particularly limited, and examples thereof include polyoxyethylene alkyl ether phosphoric acid ester and polyoxyethylene alkyl allyl ether phosphoric acid ester.
[0163] The content of the dispersant in the slurry composition is preferably 0.1 wt % or more, more preferably 0.15 wt % or more, and preferably 1.5 wt % or less, preferably 1.0 wt % or less. The content of the dispersant is preferably 0.1 to 1.5 wt %, more preferably 0.15 to 1.0 wt %.
[0164] The slurry composition may further include additives such as a plasticizer and a surfactant.
[0165] Examples of the plasticizer include bis(butoxyethyl)adipate, dibutoxyethoxyethyl adipate, triethylene glycol dibutyl ester, triethylene glycol bis(2-ethylhexanoate), triethylene glycol dicaproate, triethyl acetyl citrate, tributyl acetyl citrate, diethyl acetyl citrate, dibutyl acetyl citrate, dibutyl sebacate, glycerol triacetate, diethyl acetoxymalonate, and diethyl ethoxymalonate.
[0166] The surfactant is not particularly limited, and examples thereof include cationic surfactants, anionic surfactants, and nonionic surfactants.
[0167] The nonionic surfactant is not particularly limited, but preferably has an HLB value of 10 or more and 20 or less. Here, the so-called HLB value is a value used as an index of the hydrophilicity and lipophilicity of the surfactant. Several calculation methods have been proposed. For example, for ester-based surfactants, the following definitions are provided, that is, the saponification value is set to S, the acid value of the fatty acid constituting the surfactant is set to A, and the HLB value is set to 20 (1-S / A). Specifically, a nonionic surfactant having polyoxyethylene formed by adding an alkylene ether to a fatty chain is suitable. Specifically, for example, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, etc. can be appropriately used. It should be noted that although the above-mentioned nonionic surfactant has good thermal decomposition, if a large amount is added, the thermal decomposition of the inorganic particle dispersion slurry composition may be reduced, so the preferred upper limit of the content is 5% by weight.
[0168] The viscosity of the slurry composition is not particularly limited, but the viscosity measured at 25°C using a B-type viscometer is preferably 200 mPa•s or more, more preferably 500 mPa•s or more, and preferably 100,000 mPa•s or less, more preferably 50,000 mPa•s or less. The viscosity is preferably 200 to 100,000 mPa•s, more preferably 500 to 50,000 mPa•s.
[0169] By setting the above range, the obtained inorganic particle dispersion sheet can maintain a predetermined shape after coating by die coating printing method etc. In addition, it is possible to prevent the disadvantages such as the coating mark of the die head not disappearing, and the printability is excellent.
[0170] The method for preparing the slurry composition is not particularly limited, and a conventionally known stirring method can be cited, specifically, for example, a method of stirring the carrier composition, the inorganic particles, the dispersant, and other components such as additional solvents and plasticizers added as needed using a three-roll mill, etc. The order of adding the constituent components of the slurry composition can be appropriately set.
[0171] By using the above-mentioned slurry composition, electronic components can be produced.
[0172] Moreover, a method for producing an electronic component using the slurry composition is also one of the present invention.
[0173] Examples of the electronic components include die attach paste (ACP), die attach film (ACF), through-hole electrodes for TSV and TGV, various circuits for touch panels, RFID, sensor substrates, various die bonding agents, sealants for MEMS devices, solar cells, laminated ceramic capacitors, LTCC, silicon capacitors, electrode materials for all-solid-state batteries, etc. In addition to the above-mentioned electrode circuit uses, it can also be used for antibacterial components, electromagnetic wave shielding, catalysts, fluorescent materials, etc.
[0174] For example, the inorganic particle-dispersed molded product can be produced by applying the slurry composition onto a support film subjected to a one-side release treatment, drying the organic solvent, and then molding.
[0175] The shape of the inorganic particle-dispersed molded product is not particularly limited, but may be, for example, in the shape of a sheet.
[0176] Examples of a method for producing the inorganic particle-dispersed molded product include a method in which the slurry composition is uniformly formed into a coating film on a support film by a coating method such as a roll coater, a die coater, an extrusion coater, or a curtain coater.
[0177] For example, when the inorganic particle dispersion molded product is in sheet form, the supporting film used in manufacturing the inorganic particle dispersion molded product is preferably a resin film having heat resistance and solvent resistance and flexibility. By making the supporting film flexible, the inorganic particle dispersion slurry composition can be applied to the surface of the supporting film using a roll coater, a knife coater, etc., and the resulting inorganic particle dispersion sheet-forming film can be stored and supplied in a state of being wound into a roll.
[0178] Examples of the resin forming the support film include polyethylene terephthalate, polyester, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol, fluorine-containing resins such as polyvinyl chloride and polyvinyl fluoride, nylon, and cellulose.
[0179] The thickness of the supporting film is preferably, for example, 10 to 100 μm.
[0180] In addition, it is preferable to subject the surface of the supporting film to a release treatment, whereby the peeling operation of the supporting film can be easily performed in the transfer step.
[0181] By applying the above-mentioned slurry composition and drying it, an inorganic particle-dispersed molded product can be produced.
[0182] Furthermore, by using the slurry composition or inorganic particle-dispersed molded product as described above in a conductive paste for external electrodes, a multilayer ceramic capacitor as an electronic component can be produced.
[0183] Examples of a method for producing the multilayer ceramic capacitor include a method comprising the steps of printing a conductive paste on the inorganic particle-dispersed molded product and drying the printed conductive paste to produce a dielectric sheet, and laminating the dielectric sheets.
[0184] The conductive paste contains conductive powder.
[0185] The material of the conductive powder is not particularly limited as long as it has conductivity, and examples thereof include nickel, palladium, platinum, gold, silver, copper, molybdenum, tin, and alloys thereof. These conductive powders may be used alone or in combination of two or more.
[0186] The method for printing the conductive paste is not particularly limited, and examples thereof include screen printing, die coating printing, offset printing, gravure printing, and inkjet printing.
[0187] In the method for producing the laminated ceramic capacitor, a green ceramic laminate is produced by laminating dielectric sheets on which the conductive paste is printed, and then sintering the laminate in a reducing atmosphere at a temperature of 300 to 1500° C. to obtain a plurality of component bodies.
[0188] Then, a conductive paste for external electrodes containing the above-mentioned (meth) acrylic resin particles is applied to both end surfaces of each of these component bodies by a dipping method, and then dried at 100 to 200° C. and fired at 300 to 800° C. in a reducing atmosphere to form external electrodes at both ends of the component bodies.
[0189] Then, the external electrodes were subjected to electroplating to sequentially form a Cu film, a Ni film, and a Sn film on the external electrodes, thereby obtaining a multilayer ceramic capacitor.
[0190] Effects of the Invention
[0191] According to the present invention, a (meth)acrylic resin particle can be provided, which can provide a high-strength molded product while exhibiting excellent low-temperature decomposition properties, and can achieve further multi-layering and thin-filming, thereby being able to produce a ceramic laminate having excellent properties. In addition, a carrier composition, a slurry composition, and a method for producing an electronic component containing the (meth)acrylic resin particle can be provided. DETAILED DESCRIPTION
[0192] The present invention will be described in further detail below with reference to Examples; however, the present invention is not limited to these Examples.
[0193] (Examples 1 to 18, Comparative Examples 1 to 4)
[0194] (Production of (meth)acrylic resin particles)
[0195] A 2 L separable flask equipped with a stirrer, a condenser, a thermometer, a water bath, and a nitrogen inlet was prepared, and a total of 100 parts by weight of monomers were added to the 2 L separable flask to obtain the composition shown in Table 1. Subsequently, 900 parts by weight of water was added to obtain a monomer mixed liquid.
[0196] In addition, the following compounds were used as monomers.
[0197] MMA: Methyl Methacrylate
[0198] EMA: Ethyl Methacrylate
[0199] nBMA: n-butyl methacrylate
[0200] iBMA: Isobutyl Methacrylate
[0201] 2EHMA: 2-Ethylhexyl Methacrylate
[0202] HEMA: Hydroxyethyl Methacrylate
[0203] LMA: Lauryl Methacrylate
[0204] After nitrogen was bubbled through the obtained monomer mixture for 20 minutes to remove dissolved oxygen, the interior of the separable flask was replaced with nitrogen and the temperature was raised to 80° C. in a water bath while stirring. Thereafter, a chain transfer agent and a polymerization initiator were added in the amounts shown in Table 1 to initiate polymerization.
[0205] After 7 hours from the initiation of polymerization, the mixture was cooled to room temperature to terminate the polymerization. The obtained resin solution was then dried in an oven at 100° C. to remove water. Thus, (meth)acrylic resin particles were obtained.
[0206] In addition, the following compounds were used as a chain transfer agent and a polymerization initiator.
[0207] <Chain transfer agent>
[0208] CT-1: 3-Mercapto-1,2-propanediol
[0209] <Polymerization initiator>
[0210] KPS: Potassium persulfate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0211] VA-086: 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0212] (Preparation of Carrier Composition for Dispersing Inorganic Particles)
[0213] To 10 parts by weight of the obtained (meth)acrylic resin particles, 90 parts by weight of the solvent blended as shown in Table 3 were added, and the mixture was stirred until uniform, thereby obtaining a carrier composition for dispersing inorganic particles.
[0214] (Preparation of Inorganic Particle Dispersion Slurry Composition)
[0215] A solvent, a dispersant, and inorganic particles were added to the obtained carrier composition for inorganic particle dispersion so as to have the formulation shown in Table 4, and kneaded with a high-speed stirrer to obtain an inorganic particle dispersion slurry composition.
[0216] The solvent used in the preparation of the carrier composition for dispersing inorganic particles was used at the same ratio as the solvent.
[0217] In addition, the following compounds were used as a dispersant and inorganic particles.
[0218] <Dispersant>
[0219] Nopcosparse 092 (made by Sanyo Chemical Co., Ltd.)
[0220] <Inorganic particles>
[0221] Barium titanate (BT-02, manufactured by Sakai Chemical Industry Co., Ltd., average particle size 0.2 μm)
[0222] <Evaluation>
[0223] The (meth)acrylic resin particles and inorganic particle-dispersed slurry compositions obtained in Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 2, 3, and 5.
[0224] (1) Average carbon number of ester substituents Cp, Cs
[0225] The average carbon number Cp of the ester substituent of the (meth)acrylic resin particles and the average carbon number Cs of the ester substituent of the organic solvent were calculated by the following method.
[0226] Average carbon number Cp = cp1×wp1+cp2×wp2+···+cpn×wpn (cpn: the carbon number of the ester substituent in the segment derived from each (meth)acrylate ester constituting the (meth)acrylic resin, wpn: the weight fraction of the segment derived from each (meth)acrylate ester in the (meth)acrylic resin)
[0227] Average carbon number Cs = cs1×ws1+cs2×ws2+···+csn×wsn (csn: the carbon number of the ester substituent in each organic solvent, wsn: the weight fraction of each organic solvent in the organic solvent)
[0228] (2) Weight concentration of S atoms, weight concentration of K atoms, and weight concentration of OH groups
[0229] The weight concentration of S atoms, the weight concentration of OH groups, the weight concentration of COOH groups, and the weight concentration of K atoms contained in the (meth)acrylic resin particles were calculated by the following method.
[0230] Weight concentration of S atoms contained in (meth)acrylic resin particles = [(weight of S atoms contained in all monomers + weight of S atoms contained in all chain transfer agents + weight of S atoms contained in all polymerization initiators) / (weight of all monomers + weight of all chain transfer agents + weight of all polymerization initiators)] × 100
[0231] Weight concentration of K atoms contained in (meth)acrylic resin particles = [(weight of K atoms contained in all monomers + weight of K atoms contained in all chain transfer agents + weight of K atoms contained in all polymerization initiators) / (weight of all monomers + weight of all chain transfer agents + weight of all polymerization initiators)] × 100
[0232] Weight concentration of OH groups contained in (meth)acrylic resin particles = [(weight of OH groups contained in all monomers + weight of OH groups contained in all chain transfer agents + weight of OH groups contained in all polymerization initiators) / (weight of all monomers + weight of all chain transfer agents + weight of all polymerization initiators)] × 100
[0233] (3) Particle size
[0234] The obtained (meth)acrylic resin particles were supplied to a laser diffraction / scattering particle size distribution analyzer (LA-950, manufactured by Horiba, Ltd.) to measure the volume average particle size of the (meth)acrylic resin particles.
[0235] (4) CV value
[0236] The obtained (meth)acrylic resin particles were observed using a scanning electron microscope ("Regulus 8220" manufactured by Hitachi High-Technologies Corporation), the particle sizes of 100 particles were measured, and the CV value was calculated from the average particle size D [μm] and the standard deviation σ of the particle size using the following formula.
[0237] CV value of particle size [%] = σ / D × 100
[0238] (5) Glass transition temperature (Tg)
[0239] The glass transition temperature (Tg) of the obtained (meth)acrylic resin particles was measured using a differential scanning calorimeter (DSC).
[0240] (6) Average molecular weight
[0241] The obtained (meth)acrylic resin particles were measured for a weight average molecular weight (Mw) and a number average molecular weight (Mn) in terms of polystyrene by gel permeation chromatography using LF-804 (manufactured by SHOKO Corporation) as a column.
[0242] (7) Low temperature decomposition (TGDTA)
[0243] The obtained inorganic particle dispersion slurry composition was filled in a platinum pan of TG-DTA, and the temperature was raised from 30°C at 5°C / min in a nitrogen atmosphere to evaporate the solvent and thermally decompose the resin and dispersant. Then, the time (minutes) until 90% by weight of degreasing was completed (weight indicated 40.4% by weight) was measured.
[0244] (8) Tensile test
[0245] The obtained (meth)acrylic resin particles were dissolved in butyl acetate, and the obtained resin solution was applied to a release-treated PET film using an applicator, and dried in a 100°C forced air oven for 10 minutes to prepare a resin sheet with a thickness of 20 μm. A test piece with a width of 1 cm was prepared using scissors using a square paper as a cover film.
[0246] The obtained test piece was subjected to a tensile test at 23°C and 50RH using Autograph AG-IS (manufactured by Shimadzu Corporation) with a chuck distance of 3 cm and a tensile speed of 10 mm / min to confirm stress-strain characteristics (yield stress, elongation at break, tensile performance (yield stress×elongation at break)).
[0247] (9) Thin film test
[0248] The obtained inorganic particle dispersion slurry composition was applied to a release-treated PET film using an applicator and dried in a 100°C forced air oven for 10 minutes to prepare green sheets having a thickness of 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, and 10.0 μm after drying. Whether the green sheet was broken when peeled off from the PET film was confirmed, and the sample with the smallest thickness among the samples without breaking was used as the evaluation result.
[0249] (10) Solubility test
[0250] To 10 parts by weight of the obtained (meth)acrylic resin particles, 90 parts by weight of the solvents listed in Table 2 were added, and the mixture was heated to 50° C. while being stirred, and the stirring was continued until the resin particles were dissolved and the solution became uniform. The time from the start of stirring to the end of stirring was measured.
[0251]
[0252]
[0253]
[0254]
[0255]
[0256] Industrial Applicability
[0257] According to the present invention, it is possible to provide a (meth)acrylic resin particle that can provide a high-strength molded product while exhibiting excellent low-temperature decomposability, and can achieve further multilayering and thin-filming, thereby being able to produce a ceramic laminate having excellent properties. In addition, it is possible to provide a carrier composition, a slurry composition, and a method for producing an electronic component containing the (meth)acrylic resin particle.
Claims
1. A (meth)acrylic resin particle having a weight average molecular weight of 1.1 million or more and 5 million or less, The (meth)acrylic resin particles have a weight concentration of S atoms of 0.0020% by weight or more and 1.0000% by weight or less.
2. The (meth)acrylic resin particles according to claim 1, wherein The weight concentration of K atoms is 0.002 wt % or more and 1.000 wt % or less.
3. The (meth)acrylic resin particles according to claim 1 or 2, wherein The weight concentration of the OH group is 0.00 wt % or more and 1.50 wt % or less. 4 . The (meth)acrylic resin particles according to claim 1 , wherein the (meth)acrylic resin particles have an average particle size of 0.1 μm or more and 1.0 μm or less. 5 . The (meth)acrylic resin particles according to claim 1 , wherein The average carbon number Cp of the ester substituent calculated by the following formula is 3 to 6: The average carbon number of the ester substituent of the (meth)acrylic resin Cp = cp1×wp1+cp2×wp2+···+cpn×wpn cpn: the carbon number of the ester substituent in each (meth)acrylate segment constituting the (meth)acrylic resin; wpn: weight fraction of the segments derived from each (meth)acrylate in the (meth)acrylic resin. 6 . A carrier composition comprising the (meth)acrylic resin particles according to claim 1 and a solvent including an organic solvent.
7. The carrier composition according to claim 6, wherein The average carbon number Cs of the ester substituent of the organic solvent calculated by the following formula is 3 to 7: The average carbon number of the ester substituent of the organic solvent Cs = cs1×ws1+cs2×ws2+···+csn×wsn csn: carbon number of the ester substituent in each organic solvent; wsn: weight fraction of each organic solvent in the organic solvent.
8. The carrier composition according to claim 6 or 7, wherein The ratio Cs / Cp of the average carbon number Cs of the ester substituent of the organic solvent to the average carbon number Cp of the ester substituent of the (meth)acrylic resin particles is 0.3 to 3.
0.
9. The carrier composition according to any one of claims 6 to 8, wherein The solvent further contains 100 ppm by weight or more and 11500 ppm by weight or less of water. 10 . A slurry composition comprising the carrier composition according to claim 6 , inorganic particles, and a dispersant. 11 . A method for producing an electronic component, comprising using the slurry composition according to claim 10 .
Citation Information
Patent Citations
Binder resin for compacting ceramic
JP1998167836A
Methods for producing ceramic slurry, green sheet and electronic component
JP2011084433A